The Relationship between Class Size and Students' Achievement in English Reading Comprehension among Year 4 Students - Purrnimaa Mathavan; Rathna Devi Subramaniam; Kausalyah Markendan (Journal of Translation, Linguistics and Literature, 2024)
Class size has a significant impact on the reading comprehension of young learners. Research suggests that smaller classes can improve academic performance, including reading comprehension, by increasing student participation and individual progress. This study investigates the relationship between class size and students' achievement in English reading comprehension among Year 4 students. A quasi-experimental research design was employed, involving a mixed-methods approach incorporating quantitative and qualitative data collection methods. The results suggested that smaller class sizes have a positive impact on student's achievement in English reading comprehension compared to larger class sizes. The results of the study align with previous research, suggesting that smaller class sizes lead to better student performance. The findings of this study have implications for policy-making and educational practice, highlighting the importance of considering class size as a factor in promoting students' academic achievement.